2004
DOI: 10.1113/jphysiol.2004.065391
|View full text |Cite
|
Sign up to set email alerts
|

Human TRPC5 channel activated by a multiplicity of signals in a single cell

Abstract: Here we explore the activation mechanisms of human TRPC5, a putative cationic channel that was cloned from a region of the X chromosome associated with mental retardation. No basal activity was evident but activity was induced by carbachol stimulation of muscarinic receptors independently of Ca 2+ release. This is 'receptor activation', as described for mouse TRPC5. In addition, and in the absence of receptor stimulation, extracellular gadolinium (0.1 mM) activated TRPC5, an effect that was mimicked by 5-20 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
160
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(170 citation statements)
references
References 42 publications
10
160
0
Order By: Relevance
“…Further decreases in pH reduced the maximum amplitudes. These effects of H ϩ show striking similarities to those of La 3ϩ and Gd 3ϩ , which also activate and modulate currents through TRPC5 in a biphasic manner with potentiatory and inhibitory components at micro-and millimolar concentrations, respectively (7,13). Further evidence for similar actions of Gd 3ϩ and H ϩ was obtained in the present study at the single channel level.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Further decreases in pH reduced the maximum amplitudes. These effects of H ϩ show striking similarities to those of La 3ϩ and Gd 3ϩ , which also activate and modulate currents through TRPC5 in a biphasic manner with potentiatory and inhibitory components at micro-and millimolar concentrations, respectively (7,13). Further evidence for similar actions of Gd 3ϩ and H ϩ was obtained in the present study at the single channel level.…”
Section: Discussionsupporting
confidence: 68%
“…6). For TRPC5, additional activators have been described, the physiological significance of which is uncertain (7)(8)(9). A surprising feature of TRPC4 and TRPC5 and heteromultimeric combinations of TRPC1 and TRPC5 is their strong potentiation (10 -13) or activation (7) by micromolar concentrations of the trivalent lanthanoid cations La 3ϩ and Gd 3ϩ , effects also seen for TRPC5 with millimolar Ca 2ϩ (7,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, human TRPC5 shares greater similarity with the rabbit isoform, originally described to be store-dependent (Philipp et al 1998), than with the mouse variant. However, for human TRPC5, both store-dependent and storeindependent currents displayed similar IV relations (Zeng et al 2004). These reversed at around 0 mV, indicative of a nonselective cation channel, and displayed mainly outwardly rectifying IV relations with a weak hump positive to 0 mV.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, this study revived the hypothesis that species variants can determine whether group 4 TRPCs can be regulated in a store-operated fashion. Using the human isoform of TRPC5, which had not been studied previously at a functional level, it was shown that the channel could operate in a receptor-operated, store-independent mode and in a store-operated mode (Zeng et al 2004). The channel was activated by muscarinic receptors following a long pretreatment with thapsigargin to empty intracellular Ca 2+ stores and was thus store-independent.…”
Section: Introductionmentioning
confidence: 99%